CLASS STRUGGLE IN THE KNIGHT'S TALE MOVIE DIRECTED BY BRIAN HELGELAND: A MARXIST APPROACH - EVAWATI, DESI (2011)
The major problem of this study is to elucidate the struggle of William Thatcher reflected in Brian Helgeland's The Knight's Tale movie. The objectives of the study are; to analyse the structural elements of the movie and to analyse the character of William Thatcher based on Marxist perspective. In conducting this study, the researcher uses qualitative research in which the data are based on primary data from Brian Helgeland's The Knight's Tale movie. While secondary data are taken from references and materials related to study, whether by picking up from books and internet. In analysing the data, she applies two approaches. Firstly, structural approach is used to analyse the elements of the movie. It consists of characterization, setting, point of view, plot, style, theme, intent/ message, and cast. Meanwhile, technical elements involve mise-en-scene, cinematography, editing, and sound is analyzed to bring the readers understand totally. Secondly, the Marxist approach is used for analysing the class struggle and optimism of William Thatcher that influences his daily activity and behaviour toward life. These approaches are applied in order to get the appropriate analysis and answer the problems. The writer finds that William Thatcher's struggle leads him to an autonomous personality that has a great self confident in life.